Graduate Student Literature Review: Utilization of differential somatic cell count in the detection and management of mastitis - Burner, Carmen; Callaway, Todd R.; Ryman, Valerie E. (Journal of dairy science, 2025)
The list of standard abbreviations for JDS is available at adsa.org/jds-abbreviations-24. Nonstandard abbreviations are available in the Notes. Mastitis remains a substantial challenge for the dairy industry. Producers strive to maximize dairy cow production, health, and well-being, while also reducing antibiotic usage. Limitations to current mastitis measures have led to the exploration of the use of differential SCC (DSCC). Rather than evaluating the total cell population within milk (i.e., SCC), DSCC focuses on the distribution of individual white blood cell (WBC) types. During an infection, the number of WBC will change dramatically as a result of inflammation. Predominant WBC consist of neutrophils, macrophages, and lymphocytes. A more in-depth assessment of the immune response provided by DSCC may address limitations of other diagnostic parameters. Multiple methods exist to enumerate DSCC, with the most common being fluorescence microscopy and flow cytometry. However, there is still much unknown about the biological factors that affect DSCC. In order for DSCC to be appropriately used in the dairy industry, there must be a consensus on how DSCC is reported and a greater understanding of the physiological and environmental factors that affect cell populations. This review brings together current information on the performance of DSCC in IMI detection and related factors to help guide future directions for research.